The Effect of Giving First Aid Material for Sports Injuries Using The Rice Method on The Level of Knowledge of Students of Man 2 Kota Madiun - Delva Cinthya, Candramaya; Kaharina, Arifah (Jurnal Pendidikan Jasmani (JPJ), 2024)
First aid for sports injuries is the provision of first aid with the right procedure for someone who has an injury. One of the effective and efficient first aid methods to do is the RICE method. This study aims to determine the effectiveness of providing first aid material for sports injuries with the RICE method as an effort to improve students' knowledge about handling sports injuries. This type of research is experimental research with a quantitative approach. While this research method uses one group pre-test post-test. The population in this study were students of class XI MAN 2, Madiun City with a research sample using purposive sampling. The instruments in this study were questionnaires and the data processing techniques used were descriptive tests, normality tests, difference tests and gain tests. Based on the results of the study, it was found that there was a significant difference between the pre-test and post-test before and after being given treatment from providing material on first aid for sports injuries with the RICE method on the level of knowledge of students at MAN 2 Madiun City (p>0.05). There is a difference in the pre-test and post-test values before and after being given treatment by 3%